1976
DOI: 10.1136/jcp.29.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis, random mobility, and mobilization of polymorphonuclear leucocytes in malnutrition.

Abstract: SYNOPSIS Neutrophil mobilization following administration of Pseudomonas polysaccharide was significantly reduced in malnutrition, especially during infection. The random mobility of polymorphonuclear leucocytes (PMNs) was slightly decreased in undernutrition. Chemotactic migration of PMNs was depressed and correlated more with the presence of infection than with nutritional deficiency. It is possible that these abnormalities of PMN mobilization and mobility in malnourished individuals contribute to suboptimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

1977
1977
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…D) Diet-restricted, after fMLP. The green fluorescence intensity of peritoneal cells from the ad libitum mice was increased after fMLP stimulation (from 3 of PMNs into the peritoneal cavity at 2 hours after glycogen injection.6,7 Although we did not separate macrophages or PMNs from the peritoneal cell populations in this study, the results may reflect mainly tyrosine phosphorylation of the resident macrophages when the animals did not receive glycogen, and that of exudative PMNs after glycogen injection. 6,7 In fact, the main subpopulation of peritoneal cells in both the ad libitum and diet-restricted groups changed from macrophages to PMNs after glycogen injection (macrophages 80% to 89% and PMNs 6% before glycogen, macrophages 10% to 11%, and PMNs 70% to 71% after glycogen), according to cell differentiation of cytocentrifuged samples in a pilot study.…”
Section: Laser Scanning Cytometrycontrasting
confidence: 57%
See 1 more Smart Citation
“…D) Diet-restricted, after fMLP. The green fluorescence intensity of peritoneal cells from the ad libitum mice was increased after fMLP stimulation (from 3 of PMNs into the peritoneal cavity at 2 hours after glycogen injection.6,7 Although we did not separate macrophages or PMNs from the peritoneal cell populations in this study, the results may reflect mainly tyrosine phosphorylation of the resident macrophages when the animals did not receive glycogen, and that of exudative PMNs after glycogen injection. 6,7 In fact, the main subpopulation of peritoneal cells in both the ad libitum and diet-restricted groups changed from macrophages to PMNs after glycogen injection (macrophages 80% to 89% and PMNs 6% before glycogen, macrophages 10% to 11%, and PMNs 70% to 71% after glycogen), according to cell differentiation of cytocentrifuged samples in a pilot study.…”
Section: Laser Scanning Cytometrycontrasting
confidence: 57%
“…(journal of Parenteral and Enteral Nutrition 25:291-298, 2001) Nutrition is an important determinant of immune response.l°2 Because malnutrition is associated with high mortality and morbidity of infections,l°2 the mechanisms underlying impaired host defense during malnutrition have been sought by many investigators. [3][4][5] Protein and calorie malnutrition decreases the delayed-hypersensitivity cutaneous response, lymphocyte proliferation, DNA synthesis, complement concentration, proinflammatory cytokine production, and secretory immunoglobulin A (IgA) levels. ' Recently, we have demonstrated short-term severe diet restriction to also reduce exudative polymorphonuclear neutrophil (PMN) number in association with decreased (32-integrin expression on PMNs and chemokine levels in the peritoneal cavity in a murine glycogen-induced peritonitis model.…”
mentioning
confidence: 99%
“…All children had symptoms of cystic fibrosis and all had had at least two raised sweat sodium and chloride concentrations. At the time of entry into the trial all patients were on an unrestricted normal diet that contained a median of [3][4][5][6][7][8][9][10][11][12][13][14] (1-38-4-48) g of fat/kg/day and were receiving as their pancreatic supplement a median of 18 (6-40) capsules of Pancrease each day. Study design.…”
Section: Methodsmentioning
confidence: 99%
“…The pavementing process is related to the endothelium ionic charge and to the presence of proteins (adhesins): selectins, immunoglobulins and integrins, which may be produced by both leukocytes and endothelial cells. On the studies of Chandra & Ghai (1976) the mobilization of polymorphonuclear cells to the inflammatory site was deficient in malnourished individuals, causing a deficiency in the inflammatory process. Barja-Fidalgo et al showed for the first time that malnutrition during the first days of lactation in Wistar rats causes permanent alterations in the programming of insulin and glucocorticoid secretion.…”
Section: Discussionmentioning
confidence: 99%